Design of back-streaming white neutron beam line at CSNS. (February 2018) - Zhang, L.Y.; Jing, H.T.; Tang, J.Y.; Li, Q.; Ruan, X.C.; Ren, J.; Ning, C.J.; Yu, Y.J.; Tan, Z.X.; Wang, P.C.; He, Y.C.; Wang, X.Q.
Abstract: A white neutron beam line using back-streaming neutrons from the spallation target is under construction at China Spallation Neutron Source (CSNS). Different spectrometers, to be installed in the so-called Back-n beam line for nuclear data measurements, are also being developed in phases. The physical design of the beam line is carried out with the help of a complicated collimation system and a sophisticated neutron dump, taking the overview of the neutron beam characteristics into account. This includes energy spectrum, flux and time structure, the optimizations of neutron beam spots and in-hall background. The wide neutron energy range of 1 eV–100 MeV is excellent for supporting different applications, especially nuclear data measurements. At Endstation#2, which is about 80 m away from the target, the main properties of the beam line include neutron flux of 10 6  n/cm 2 /s, time resolution of a few per mille over nearly the entire energy range, and in-hall background of about 0.01/cm 2 /s for both neutron and gamma. With its first commission in late 2017, Back-n will not only be the first high-performance white neutron source in China, but also one of the best white neutron sources in the world. Highlights: First white neutron source (Back-n) based on China Spallation Neutron Source is designed for nuclear data measurements. The transport, collimation and shielding of white neutron beam have been simulated by using FLUKA code. Optimizations of neutron beam-spot size, uniformity and intensity are studied in detail.